The effects of content-based instruction on listening and speaking abilities of Thai EFL university students / Yuanxing La and Prachamon Aksornjarung - Yuanxing, LaI; Prachamon, Aksornjarung (Universiti Teknologi MARA, Kedah, 2017)
This research investigated the effects of a 14-week content-based instruction (CBI) English course on Thai EFL learners' listening and speaking abilities. Eighty-one Thai university students were enrolled in the CBI English course titled Learning English Through Cultures which employed the teaching approach of content-based instruction for one academic semester. A computerized test o listening and speaking was developed and administered with students as a pre-test before the CBI teaching and as a post test after the instruction. Classroom observations were also conducted by the researcher by sitting in the class and taking notes. The qualitative data was triangulated with the quantitative testing results. Results revealed a significant increase in speaking and listening among all students. The students in the low proficiency group especially made a significant advance in both speaking and listening, compared with students in the high proficiency group who only showed a significant development in speaking. It is advisable that the course book or the teaching materials should be attractive to students. Further, it is suggested that scaffolding should be provided in various forms and CBI teaching should consider the needs of students at different levels of English proficiency. Future studies may apply a retention test and have a control group with a focus on improving specific aspects of listening abilities.